Strengthening youth associations in creating the “Merehat” (be educated literacy in numeracy, technology, and health) generation at SMA Muhammadiyah Bangka Belitung - Agustine, Putri Cahyani; Mega, Iful Rahmawati; Walton, Erick Prayogo; Pratama, Yudistira Bagus; Azzani, Arlina Feijriah; Fermanda, Syandhu Dea; Putri, Elsa Hana Rahma; Christivo, Ryevilgo (Abdi Masyarakat, 2025)
This community service activity was carried out to introduce an understanding of literacy and numeracy, the use of technology in learning and understanding the importance of adolescent health awareness which is a contribution to the problems in the field, there is a lack of productivity of adolescents in the organization 1) less time to study especially for numeracy literacy content, 2) lack of ability to utilize technology in learning, 3) lack of understanding of adolescents in the organization in handling injuries during activities and lack of awareness of adolescents in maintaining health. The training was conducted at SMA Muhammadiyah Pangkalpinang, and 30 high school students participated. The results of this activity are the presentation of material on understanding literacy and numeracy, an introduction to making flyers with Canva, and an introduction to a healthy lifestyle. This activity has been published in local mass-media articles in Bangka Belitung, and the videos have been uploaded on the official LPPMPP YouTube account of Universitas Muhammadiyah Bangka Belitung. The participants from this event hope that the activity will always be carried out periodically because the participants' feedback was great, indicating a percentage of 83.57%.